Enhancing the Role of Information Technology in the Organizations: An Analytical Studyfor the Opinions of a sample of Employeesin the of the Muunicipality of Erbil - Mazin Tmir Agha (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The research seeks to study strengthening the role of information technology in organizations in the city of Erbil for the year 2020-2021 (an applied study in the municipalities of the city of Erbil). It is an analytical study of the views of municipalities. Information technology is represented as an excluded variable and depends on (3) dimensions, which are (software, communication networks, requirements for using IT). Organizations (municipalities) are represented as an approved variabledepends on (2) dimensions,) style of the operations in the organization, level of performancein the organization. To reach the objectives of the research, it relied on the two approaches (descriptive and analytical). The number of (6) municipalities. The questionnaire was distributed to them and it was relied upon as a tool for collecting data and information. Then the researcher developed a hypothetical model based on a set of hypotheses, the most important conclucions reached by the research is the existence of a significant correlation and influence between technology in organizations, the research also recommended stregtheing the wake relationship between communication network and organizations by increasing the interest of municipalities on modern technology in completing its work.